Biblical Narrative in a Century of Newspapers - Terje Stordalen (Svensk Teologisk Kvartalskrift)
This essay gives a macroscopic view of the space of biblical narrative in Norwegian newspaper discourse in the 20th century. The digital repository of the National Library of Norway (NLN) gives access to all Norwegian Newspapers printed since 1814. A so-called Ngram search in this repository shows that newspaper references to the Bible increased drastically during the 20th century, with a peak in the 1990’s, featuring almost seven times more hits than in the 1910’s. One reason for this increase was the change of newspaper editorial policy after radio and TV became mass media. The newspapers started reporting more “slow news”, and the frequency of biblical references is much higher in this material. Cultural products, like novels, films, and especially TV programs, contributed massively to the increase. Concentrating on tracing ten biblical narratives, the essay shows that references to individual stories could peak in different decades. It also asks what societal segment newspapers mirror when referring to biblical stories. It turns out that use of biblical stories in the cultural sector is the most important. Some stories appear in advertising etc. from business life. Very few references to biblical narratives in ecclesial use are found in the newspapers. The findings illustrate the presence of a “public Bible” and the complexity of secularization in Scandinavia. They also open new questions concerning the study of reception of biblical narratives and, indeed, the study of the Bible in the university.